STUDI KELAYAKAN INVESTASI BISNIS PROPERTI (STUDI KASUS: CIATER RIUNG RANGGA) - Warsika, Putu Dharma (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 1 Januari 2009)
It has been long time that government (regulator), developer (organizer) and banking side (source of finance) are trapped in wrong assumption of seeing business of property. The government assumption that development of big scale housing area (by development of new town or self-supporting town) will create efficiency at national industry housing in fact is totally wrong. Developer and banking side opinion which say that by using business calculation big scale property will give more benefits than those of small scale project. Logically, the greater the project property the higher the price of the land and the house to be sold to the consumer but it lacks of buyer. Ciater Riung Rangga is one of property projects which were launched in 1995 and invested a big capital in long term. The question arises whether investment to that project will benefit or not. Analyses such as cash in flow, cash out flow, projected cash flow, NPV, IRR, Profitability index, Modified IRR and COC are used to analyze the data. Base on the research conducted total cash in flow and cash out flow of the Ciater Riung Rangga project were Rp190.772.079.000,- and Rp121.493.750.000,- respectively. Projected Net profit was Rp35.202.956.100,-. NPV obtained was Rp14.848.189.000,- indicating that this project was competent to be run. Result of IRR was 69,38 % (greater than 20%), which means that the project was feasible to be run. Profitability Index/ ratio was >>> 1, with assumption that initial investment was zero. Result of MIRR was 33, 42% and COC was 25,76%, meaning that it can be reinvested (MIRR > COC).
Keywords: feasibility study, investment, property.